REVIEW ON FOG COMPUTING – APPLICATIONS, SECURITY, AND SOLUTIONS - Varun Varma Sangaraju; SV Achuta Rao; Amjan Shaik; Prasuna VG; Nagaraju P B S.R.K.R. (Proceedings on Engineering Sciences)
A distributed computing model known as fog computing lies near the user for efficient data processing and analysis. Fog computing extends cloud computing and expands on the characteristics providing more features for the consumer's benefit. A flexible fog computing architecture gives service providers and organizations a significant advantage in developing better systems. Fog computing boasts a plethora of applications across various industries. However, fog computing adopts the same security and privacy issues as cloud computing. Fog computing security and privacy issues were researched extensively and presented in this paper. This research also discusses the possible security configurations existing for the fog computing environment.